Dominican Republic : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 1995)
This paper examines the Uruguay Round and its implications for the Dominican Republic. The ratification of the Uruguay Round Agreement has several implications for the Dominican Republic. Certain regulatory and legislative reforms will have to be addressed, some new specific institutional mechanisms developed, and several commitments will have to be implemented. In addition, the competitiveness of the Dominican Republic regarding several export products may be affected. The paper highlights that the Dominican Republic has committed to unifying all import charges to no more than a harmonized level of 40 percent.